Critical Evaluation of Indonesia's Maritime Security Governance Post-Government Regulation No. 13 of 2022 from a Whole-of-Government Perspective - Supriady , Ferry; Winarno, Umar; Faisol, Achmad (Journal of Industrial Engineering & Management Research, 2026)
The complexity of Indonesia's maritime security governance is characterized by dualism of authority and acute institutional fragmentation. The phenomenon of multiple agencies with overlaGovernment Regulationing authority has created state budget inefficiencies and operational confusion in maritime law enforcement. The purpose of this study is to critically evaluate the effectiveness of Government Regulation (Government Regulation) Number 13 of 2022 concerning the Implementation of Security, Safety, and Law Enforcement in Indonesian Waters and Jurisdiction as an instrument of national policy integration. Using normative legal research methods with a statutory, comparative, and conceptual Whole-of-Government (WoG) aGovernment Regulationroach, this study uncovered a regulatory paradox. Although Government Regulation No. 13 of 2022 mandates the Maritime Security Agency (Indonesian Coast Guard) as coordinator, this regulation remains stuck at the level of "administrative coordination" without addressing the aspect of "operational command integration." In-depth analysis shows that the Government Regulation's hierarchical status below sectoral laws render Indonesian Coast Guard lacking coercive power over other agencies such as the Marine and Fisheries Service (KPLP) and the Water Police. Without a Maritime Security Omnibus Law that unifies assets and command, Indonesia is vulnerable to hybrid threats in the North Natuna Sea due to a fragmented response.